Uji Kausalitas Hubungan Antara Penyesuaian-Penyesuaian Dalam Metode Perbandingan Data Pasar Dan Opini Nilai Properti Komersial - Setijono, Djoko (Seminar Nasional Official Statistics, 2024)
Despite the existence of publications presenting methods and/or techniques to determine the magnitude of certain adjustments in a valuation using Comparable Method, there are few (or perhaps none) publications that have attempted to test the causal relationship between valuation adjustments with the opinion of market value. Such lack or scarcity might be caused by the fact that the testing requires the researcher to directly observes the logic of the respondents when making adjustments prior to reaching a conclusion regarding the market value of an asset (property). Multiple Regression Analysis conducted on the answers of 61 respondents, collected using Survey Experiment, concludes that Dimensional Adjustment and Location/Position Adjustment have significant causal relationship with Market Value estimate. Hence, professional valuers need to pay attention towards dimensional and location/position equality (comparability) when selecting which comparable data to use in the valuation of a commercial property and considerably determine the magnitude of those adjustments.